2016
DOI: 10.21107/jaffa.v4i1.1880
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi, Gaya Kepemimpinan, Sistem Informasi Akuntansi Dan Standar Akuntansi Pemerintah Terhadap Kinerja Organisasi Pada Pemerintah Daerah Kabupaten Sumbawa

Abstract: <p><em>This study was conducted to examine the influence of organizational culture , leadership style , accounting information systems and government accounting standards on organizational performance Sumbawa Regency government . Objects in this study are echelon II , III Echelon and Echelon IV. Respondents were asked to answer a list of questions in the questionnaire form</em></p><em>Distribution of the questionnaire as many as 90 copies to all agencies , but which can be analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…The results of this research are in line with previous research conducted by Fadhlurrohman, Budiman, and Khairina (2021), Sadad, Pituringsih and Irwan (2016), and Syahputri et al, (2019) which stated that organizational culture affects the performance of local government organizations. However, the results of this research contradict Indudewiet al, (2021) based on his research in Regional Apparatus Organizations (RAO) at the Yogyakarta Special Region Government (DIY) which concluded that organizational culture in a high context had no effect on government performance.…”
Section: Organizational Culture On the Performance Of Government Agen...supporting
confidence: 91%
See 2 more Smart Citations
“…The results of this research are in line with previous research conducted by Fadhlurrohman, Budiman, and Khairina (2021), Sadad, Pituringsih and Irwan (2016), and Syahputri et al, (2019) which stated that organizational culture affects the performance of local government organizations. However, the results of this research contradict Indudewiet al, (2021) based on his research in Regional Apparatus Organizations (RAO) at the Yogyakarta Special Region Government (DIY) which concluded that organizational culture in a high context had no effect on government performance.…”
Section: Organizational Culture On the Performance Of Government Agen...supporting
confidence: 91%
“…The results of this research are in line with previous research conducted by Sadad, Pituringsih and Irwan (2016) which stated that accounting information systems have no effect on government performance, and Ahmad and Sybiel (2019) based on their research in the SME industry in Jordan, concluded that information systems accounting has no significant effect on company performance. However, this research contradicts the results of previous studies which proved that accounting information systems are effectively used to improve organizational performance (Ismail, 2009), business performance (Abu Shahan et al, 2015), and local government performance (Molan and Priyadi, 2020).…”
Section: Accounting Information System On the Performance Of Governme...supporting
confidence: 89%
See 1 more Smart Citation
“…The results prove that leadership style influences organizational performance in the public sector. At the same time, research from (Sadad, 2016) and (Aprila, 2013) revealed that the leadership style did not affect the performance of the SKPD.…”
Section: Introductionmentioning
confidence: 94%